Riskonnected: Social Media, Puberty and Risky Behaviours in Adolescence - Margherita Agnoletto; Marina Della Giusta; Silvia Mendolia (Institute of Labor Economics (IZA), 2025)
We examine the impact of intensive social media use on puberty timing, particularly earlier menarche in girls. Using data from the Millennium Cohort Study (MCS), a nationally representative longitudinal dataset tracking around 19,000 children in the UK, we analyse how digital engagement influences adolescent development. Our results show that intensive social media use significantly accelerates menarche in girls but has no clear effect on male puberty markers. The likely mechanism behind this effect is the negative impact of social media on mental health, particularly stress and anxiety, which have been linked to earlier menarche. Our findings highlight social media use itself as a potential risky behaviour, reinforcing concerns about its effects on adolescent well-being.
Keywords: I12; I31; J13; J16; 330; menarche; stress; social media; risky behaviours